2016
DOI: 10.1155/2016/2574637
|View full text |Cite
|
Sign up to set email alerts
|

Menoprogen, a TCM Herbal Formula for Menopause, Increases Endogenous E2in an Aged Rat Model of Menopause by Reducing Ovarian Granulosa Cell Apoptosis

Abstract: The effect of Menoprogen (MPG) on ovarian granulosa cell (GC) apoptosis was investigated in vitro and in vivo in an aged rat model of menopause. Intragastric administration of Menoprogen or estradiol valerate to 14-month-old senile female rats for eight weeks increased plasma E2 levels, as well as the weight of both ovarian and uterine tissues. Flow cytometric (FCM) analysis of isolated GCs from MPG-treated aged rats showed reductions in the G0/G1 ratio and apoptotic peaks. Isolated GCs also exhibited an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…GCs play a crucial role in female reproduction by synthesizing sex hormones, including E 2 and P 4 , as well as interacting with the oocytes [ 28 , 29 ]. Therefore, we speculate that IRS2 may participate in steroid hormone synthesis to regulate follicular growth and ovarian steroidogeneses.…”
Section: Discussionmentioning
confidence: 99%
“…GCs play a crucial role in female reproduction by synthesizing sex hormones, including E 2 and P 4 , as well as interacting with the oocytes [ 28 , 29 ]. Therefore, we speculate that IRS2 may participate in steroid hormone synthesis to regulate follicular growth and ovarian steroidogeneses.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2008 we have been investigating a TCM herbal formula Menoprogen (MPG) [14,15,16,17,18,19], which has been shown to reduce menopausal symptoms and the Kupperman index in Chinese women [15]. This formula contains five medicinal and food plants, and has been used in China for centuries to treat menopausal symptoms [14,15,16,17,18,19]. In our previous work, we have shown that the mechanism of MPG is very novel in that it does not act as a phytoestrogen, but works indirectly by reducing GC apoptosis via a mechanism involving IGF-1.…”
Section: Discussionmentioning
confidence: 99%
“…Herbal medicines, including traditional Chinese medicines (TCM), are used in most countries worldwide for the management of menopausal symptoms [13,14,15,16,17,18,19]. In a pilot observational clinical trial, we have demonstrated that treatment of menopausal Chinese women with a TCM formula named Menoprogen (MPG) that contains five medicinal herbs, including Morus alba L .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dosage of administration was 2 mL/200 g, twice a day, and continuous administration for three days. Three days later, fundus blood from Wistar rats was obtained 2 h after gavage administration to obtain serum in order to investigate the effect of the prescriptions on SKOV3 tumor cell lines [ 43 , 44 ]. After incubation under 5% CO 2 at 37 °C for 24 h, SKOV3 cells (10 4 cells per well) were subsequently inoculated onto 96-well plates.…”
Section: Methodsmentioning
confidence: 99%